Kajian Kerentanan Iklim: Sebuah Penilaian Kembali di Wilayah Pesisir Kota Semarang - Fauziah, Annisa Nur (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Behind the dynamic growth of this coastal city, Semarang have to deal with the issue of global climate change such as erotion, flood, land subsidence, sea level rise and ecosystem degradation. Based on that, we combined field data from 100 households in 14 sub-districts of Semarang coastal communities with secondary data to collect data on biophysical and sosio-economic impacts of climate variability, secure tenure index, sosio-demographic profile, livelihood, education level, institutional, livelihood strategy, and adaptation technology. The results of analysis suggest that 3 among 14 districts of Semarang coastal areas had very high level of climate vulnerability. They were Mangkang Wetan, Bandarharjo, and Tanjung Mas districts. Mangkang Wetan was more vulnerable than the other sub-district particularly in relation to social-demographic profile, livelihood, institutional, and livelihood strategy. While Bandarharjo was more vulnerable in relation to biophysical and sosio-economic impacts of climate variability, social-demographic profile, and secure tenure index. Then Tanjung Mas was more vulnerable in terms of biophysical and sosio-economic impacts of climate variability, livelihood strategy, and adaptation technology. In this regard, this approach may be used to facilitate climate vulnerability by minimize contributing factors of vulnerability or enhance the communities ability to cope with the impacts of climate change.